A Rare Case of Metastasis to the Thyroid Gland from Renal Clear Cell Carcinoma 11 Years after Nephrectomy and Concurrent Primary Esophageal Carcinoma. (2nd April 2018) - Khan, Mohammad Saud; Iyer, Veena Balakrishnan; Varshney, Neha
Abstract : Renal cell carcinoma is known to cause metastasis to unusual sites, which can be both synchronous or metachronous. Thyroid gland is a rare site for metastasis, but when it occurs, renal cell carcinoma is the most common primary neoplasm. We report the case of a 81-year-old female patient who had a significant medical history of right clear cell renal carcinoma with adrenal metastasis. She underwent right radical nephrectomy and adrenalectomy followed by radiofrequency ablation of left adrenal metastasis and systemic chemotherapy with sunitinib. Eleven years later, she presented with dysphagia and was found to have distal esophageal adenocarcinoma. On imaging, there was incidental detection of a left renal mass lesion and a right thyroid nodule, which on histopathology and immunohistochemistry were confirmed to be clear cell carcinoma of renal origin.